Optimasi Penyerapan Zat Warna Malachite Green Menggunakan Karbon Aktif dari Kulit Pisang Kepok (Musa balbisiana Colla) - Sintha Hafizhah Yonel; Edi Nasra; Budhi Oktavia; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2021)
Malachite green is a synthetic dye that is widely used in the textile industry. Textile industry waste that is not treated properly will pollute the aquatic environment. The threshold value for the permissible concentration of Malachite green in waters is around 0.01 mg/L. The adsorption method is an alternative method used to remove dyestuff waste. This study used a batch method which aims to determine the optimum conditions for absorption and the maximum absorption capacity of Malachite green using activated carbon from the peel of Kepok banana (Musa balbisiana Colla). In this study, treatments were carried out using variations in solution concentration and contact time. The results of this study, obtained the absorption capacity at optimum conditions concentration 150 mg/L and contact time 150 minutes with absorption capacity of 9.2429 mg /g with absorption percentage of 97.9734%. Mechanism the absorption of Malachite green follows the equation Langmuir isotherm with a determinant coefficient (R2) of 0,9989.